Recent Advances in the Synthesis of Oxazole-Based Molecules via van Leusen Oxazole Synthesis - Zheng, Xunan (Molecules, 2020)
Oxazole compounds, including one nitrogen atom and one oxygen atom in a five-membered heterocyclic ring, are present in various biological activities. Due to binding with a widespread spectrum of receptors and enzymes easily in biological systems through various non-covalent interactions, oxazole-based molecules are becoming a kind of significant heterocyclic nucleus, which have received attention from researchers globally, leading them to synthesize diverse oxazole derivatives. The van Leusen reaction, based on tosylmethylisocyanides (TosMICs), is one of the most appropriate strategies to prepare oxazole-based medicinal compounds. In this review, we summarize the recent advances of the synthesis of oxazole-containing molecules utilizing the van Leusen oxazole synthesis from 1972, aiming to look for potential oxazole-based medicinal compounds, which are valuable information for drug discovery and synthesis.